Pre-Service English Teachers’ Use of Total Physical Response (TPR) in Young Learners’ Online and Offline English Lesson - Aqila, Fayza; Astuti, Irma Windy (Prominent, 2025)
Numerous studies have explored the implementation of Total Physical Response (TPR); however, most have primarily focused on offline teaching contexts. This study aims to describe the implementation of TPR in both online and offline young learners' English lessons. A qualitative descriptive approach was employed, with classroom observations as the primary data source and interviews serving as supplementary data. The observation instrument was based on the 13 principles of TPR outlined by Larsen-Freeman and Anderson (2011). The participants were two female pre-service English teachers: one teaching offline and the other online. The findings indicate that both teachers were unable to fully optimize the application of TPR in their respective settings. The observation results revealed variability in the number and frequency of TPR principles applied by each teacher, with some principles being implemented consistently, others infrequently, and some not at all. The interview data confirmed that the implementation of TPR was shaped by various factors perceived as either advantages or challenges in each context. The study suggests that teachers’ knowledge and experience with TPR are critical factors influencing the effective implementation of TPR in both online and face-to-face classrooms.